Model peralihan jisim serentak bagi titisan-titisan yang pelbagai saiz - Ayob, Syafikah (2013)
Liquid-liquid extraction is one of the important transfer operations in chemical engineering. In the design of extraction equipment, basic understanding of the mechanism of mass transfer between disperse phase and the continuous phase is very important. Typically, this problem is solved by means of measuring the mass transfer rate obtained from rotating disc extraction column (RDC) that was predicted by the model of simultaneous mass transfer. Because the mass transfer rate depends on several factors which sometimes can not be measured accurately, as the form of drops, drop size and the differences that occur in the RDC column. This study focuses on the modeling of the diffusion problem in different sizes of drop size in a stage of RDC column using the concept of diffusion in spherical drop with the assumption that the diffusion process from the continuous phase to the disperse phase occur simultaneously. Next, the simulation process for the mass transfer process of 10 drops with various sizes in a stage is done using simultaneous mass transfer model.